KEBERADAAN GO JEK SEBAGAI ALAT TRANSPORTASI ONLINE DITINJAU DARI SISTEM PERIZINAN (Studi Kota Pontianak) - NPM. A2021141019, YOUNG HENDRIYANA, SH (Jurnal NESTOR Magister Hukum, 2018)
ABSTRACT This thesis discusses the aspect of permission and efforts of Pontianak City Government to the existence of Go-Jek Online which is not only located in big Indonesia but also in various cities throughout Indonesia, including in Pontianak city, beginning of 2017 until now the ojek user online has been perceived by community as an online service user, various reasons and arguments presented by the positive community, in addition to easily accessible, low cost, and fast, it also provides a solution in the field of transportation. Behind the positive community response there is another issue, by the policy makers in this case the Pontianak Municipal Government that requires regulation of the arrangement of Go-Jek-based grants online dipontianak,